Transfer pricing - Newton, Basil (Department of Commercial Law, 2021)
"Today, transfer pricing is about the a/location of income of a multinational enterprise between nations. The introduction of anti-avoidance provisions were in th~ main sufficient to deter companies from shifting profit to overseas associates through under or over pricing of cross border transactions. Tax avoidance, was at the centre. Tax avoidance, today if present, is at the margins, not at the centre. Transfer pricing is a neutral concept. Often, it is used incorrectly in a pejorative sense, to mean a pricing decision by a multinational enterprise which shifts income from one member of a group to another." Transfer Pricing Strategy in a Global Economy by Jill C.Pagan and J Scott Wilkie.